Basics of Islamic Education Management - Deskasari, Sri; Yarnita, Yetti; Wendra, Zetria; Yuliani, Tri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Islamic Education Management is an educational management site that applies Islamic teachings that aim to create an intellectual, moral and positive educational environment. The purpose of this study is to find out the basics of Islamic education management. Qualitative is the method used in this study with a literature review study. This study was conducted by reviewing reading sources related to the research topic discussed, as well as reviewing study documents from previous studies related to the concept. Data were collected by looking at books, scientific journals, and digital sources. The results obtained are that Islamic Education management includes planning, organizing, implementing, supervising, and evaluating which are carried out in an integrated manner with Islamic values.